The impact of net value added on predicting the earnings and operating cash flow: An empirical study based on Tehran Stock Exchange - Omid Imani Khoshkhoo; Seyed Reza Seyed Nezhad Fahim; Masoud Mokhtari (Management Science Letters, 2013)
Information content of earnings and its components and other issues except the earnings such as the operating cash flow (OCF) have been tested widely in the accounting and finance literature. Since they have had an essential role in most cases including financial reporting, contracts and evaluation models, specifying the items and financial variables that have had a significant relationship with these two variables are expected to be of utmost importance. One example of these variables and indicators is the value added. Although this variable has an economic concept, reporting of value added to the beneficiaries of business entity as the value-added statement has been observed in the field of accounting theories for many years. The main objective of this study was to investigate the effect of net value added (NVA) as the basic result of value-added statement in predicting the accounting earnings and operating cash flow. For this purpose, the relationship of changes in net value added with the changes in accounting earnings and operating cash flow of listed companies in Tehran Stock Exchange from 2007 to 2011 was tested. Firstly the Single variable cross-sectional regression was analyzed and then the panel data analysis with the PLS technique was used to do a pooled analysis. The results of testing research hypothesis imply the significant relationship between changes in net value added and accounting earnings in the listed companies as cross-sectional and pooled forms. The results showed no significant relationship between changes in net value added and operating cash flow in the listed companies neither in cross-sectional nor pooled form.